Intrabubble coupled evolution of microdroplets and nanobubbles in oxygen evolution reaction - Congfan Zhao; Shu Yuan; Jiabin You; Chenyun Bai; Yongjian Su; Xiaojing Cheng; Shuiyun Shen; Xiaohui Yan; Junliang Zhang (Proceedings of the National Academy of Sciences, 2026)
In the oxygen evolution reaction (OER), adherent gas bubbles are conventionally viewed as a major impediment that blocks ion and mass transport by covering active sites. Here, we show that for ionomer-based electrodes, this prevailing view is oversimplified. Using a self-developed transparent on-chip electrolyzer that integrates multimodal in-situ characterization, including optical microscopy, spectroscopic analysis, and atomic force microscopy, we uncover complex intrabubble dynamics on ionomer-coated electrodes. During bubble growth, the three-phase contact line exhibits characteristic pinning–depinning behavior. Beyond a critical bubble size (~420 μm), free water molecules are evolved from the ionomer into the bubble–electrode contact area, forming microdroplets (<20 μm) that continuously coalesce. Inside these microdroplets, oxygen products further nucleate as pancake-shaped nanobubbles (~50 nm), revealing a previously unrecognized intrabubble process. We find that this coupled microdroplet–nanobubble evolution is enabled by the phase-separation behavior of ionomer. The ionomer also preserves local electrochemical activity even under substantial bubble coverage, unlike ionomer-free electrodes where bubble blockage leads to severe deactivation. By tailoring ionomer phase separation, we achieve intensified microdroplet–nanobubble evolution and measurable performance improvement at high current densities. This finding opens a route to mitigate bubble-induced activity loss in OER electrodes.